2014
DOI: 10.1021/cb500209a
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationship of Thiazolide-Induced Apoptosis in Colorectal Tumor Cells

Abstract: Thiazolides are a novel class of anti-infectious agents against intestinal intracellular and extracellular protozoan parasites, bacteria, and viruses. While the parent compound nitazoxanide (NTZ; 2-(acetolyloxy)-N-(5-nitro-2-thiazolyl)benzamide) has potent antimicrobial activity, the bromo-thiazolide RM4819 (N-(5-bromothiazol-2-yl)-2-hydroxy-3-methylbenzamide) shows only reduced activity. Interestingly, both molecules are able to induce cell death in colon carcinoma cell lines, indicating that the molecular ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…Although we have initially seen that thiazolides bind to GSTP1-1 and inhibit the enzymatic activity of GSTP1-1 in vitro , very likely this observation was based on substrate competition. Indeed, we have seen later that enzymatic GSTP1-1 activity is required for thiazolides to kill colorectal tumor cells, and that increased GSH levels enhance thiazolide activity 31 , 32 ( Figure 6a ). Thus, very likely GSTP1-1 couples GSH to thiazolides, and thereby generates active apoptosis-promoting products.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although we have initially seen that thiazolides bind to GSTP1-1 and inhibit the enzymatic activity of GSTP1-1 in vitro , very likely this observation was based on substrate competition. Indeed, we have seen later that enzymatic GSTP1-1 activity is required for thiazolides to kill colorectal tumor cells, and that increased GSH levels enhance thiazolide activity 31 , 32 ( Figure 6a ). Thus, very likely GSTP1-1 couples GSH to thiazolides, and thereby generates active apoptosis-promoting products.…”
Section: Discussionmentioning
confidence: 89%
“…We have previously performed a structure-function study and shown that changes of substituents in the benzene ring do not affect the cell death-promoting activity of thiazolides, whereas removal of the bromide atom from the thiazole ring, as in compound 2, strongly reduces the activity. 32 To investigate the thiazolide-induced apoptosis signaling pathways, we employed RM4819 as an active thiazolide, and compound 2 is inactive control substance to induce apoptosis in the colorectal tumor cell lines Caco-2 and LS174T. Figure 1a (Caco-2 cells) and Supplementary Figure 1 (LS174T cells) show that RM4819 induced cell death in a dose-dependent manner, whereas cells were almost insensitive to compound 2.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, we demonstrated that luteolin activated some enzymes of a DNA damage pathway resulting in significant toxicity for OSCC cells. Moreover, although nitazoxanide was previously shown to be efficient against other cancer cells, such as colorectal (31)(32)(33)(34) and breast cancers (35), the antitumoral activity of metixene hydrochloride and nitazoxanide had not previously been demonstrated against oral cancer cells. We report here that luteolin, metixene hydrochloride, and nitazoxanide exhibit dose-and time-dependent selective toxicity in SCC-25 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, apresenta baixa toxicidade contra tecidos normais e efeitos colaterais brandos (Broekhuysen et al, 2000;Cohen, 2005). O efeito antitumoral da nitazoxanide foi descrito em câncer colorretal, de mama, linfático, ósseo in vitro e in vivo (Muller et al, 2008;Sidler et al, 2012;Fan-Minogue et al, 2013;Brockmann et al, 2014;Senkowski et al, 2015). A luteolin é um flavonoide pertencente ao subgrupo das flavonas e foi identificada em mais de 300 espécies de plantas e vegetais.…”
Section: Lista De Ilustraçõesunclassified
“…Em 2014, foi publicado outro trabalho demonstrando que o BRM4819 é capaz de induzir a apoptose em três linhagens de câncer colorretal. Esta atividade pró-apoptótica é dependente da ativação da caspase-3 e da expressão do GSTP1 (Brockmann et al, 2014 …”
Section: Nitazoxanideunclassified